DETERMINANTS OF LEVEL OF DECLARED PHYSICAL ACTIVITY OF BELARUSIAN STUDENTS - Baj-Korpak, J.; Shpakou, A.; Korpak, F.; Szepeluk, A. (Theory and Practice of Physical Culture, 2022)
Background. The current state of the knowledge of determinants of the level of physical activity is still insufficient. Objective of the research was to determine the level of declared physical activity undertaken by students of Belarusian universities and to learn about its determinants. Methods and structure of the study. In the studied group, women constituted a greater percentage (75.8% of all respondents). The research was carried out using the diagnostic survey method using the long version of the International Physical Activity Questionnaire - IPAQ, with its own modification. For the purposes of this study, questions about the self-assessment of the level of physical activity and the budget of free time were added to the IPAQ record. Results and conclusions. It was found that nearly 60% of the surveyed youth show a high level of physical activity. The determinants included in the statistical analysis (gender, self-assessment of the level of physical fitness and the amount of free time) were statistically significant. Men turned out to be more active than women. A greater proportion of respondents with a BMI indicating overweight were more active than those with a normal BMI or those who were underweight. High self-esteem and declaration of not having free time by the surveyed youth are associated with a higher level of physical activity. The higher the physical fitness self-assessment, the higher the respondents' physical activity.